Mixing intensification in Carreau–Yasuda fluid promoted by magnetohydrodynamic flow manipulation - a numerical study - Chitradittya Barman; Aditya Bandopadhyay (Flow)
In this work, three-dimensional numerical investigations into flow manipulation have been conducted using the principles of magnetohydrodynamics, followed by the analysis of the phenomenon of species mixing in a Carreau–Yasuda-type fluid. The flow control has been implemented by employing Lorentz forces to guide the conducting fluid along desired routes throughout a compact mixing chamber. The Lorentz forces were generated using electrode arrays placed in a magnetic field. We have demonstrated that different flow patterns can be created by using different electrode configurations with minor variation in the applied electrode potentials. Results show that the mixing performance of the device depends on the electrode configuration and rheology of the fluid – shear thinning, Newtonian or shear thickening. Effects of fluid rheology on different aspects of flow and mixing have been thoroughly investigated.